Fermentation of Spinach (Amaranthus spp) and Broccoli (Brassica oleracea L.) Using Kombucha Culture as Natural Source of Folic Acid for Functional Food - Melanie, Hakiki; Susilowati, Agustine; Maryati, Yati; Lotulung, Puspa D. (IPTEK Journal of Proceedings Series, 2017)
The importance of folate (folic acid, B9 vitamin, pteroyl-L-glutamic acid) in human diet for the prevention of neural tube defects during pregnancy is widely known. Green vegetables are known to be a potential source of natural occurring folic acid instead of legumes and grains. The fermentation process using a mixed culture of kombucha is an alternative of natural folic acid production from green vegetables. Broccoli and spinach was selected based on its folic acid content compared to other vegetables. This research was conducted by the extraction of broccoli and spinach at 80 °C with a ratio of vegetable and water of 1:4. The inoculum was obtained by inoculating kombucha culture on vegetable extracts for 7 days at room temperature. The vegetable extracts were then fermented using inoculum with concentration of 15, 25 and 35% (v/w of polyphenol of vegetable extracts) for 0, 3, 6, 9, 12 and 15 days at room temperature. The analysis were performed on total solids, polyphenol, dissolved protein, reducing sugars, amylase and protease activities, total acid, total plate counts and folic acid contents. This study showed that the type of vegetables, inoculum concentration and fermentation time affect the chemical composition of fermented vegetables. Fermented broccoli and spinach with inoculum concentration of 15% had the highest yield of folic acid of 69,52 µg/mL and 62,05 µg/mL after 6 days and 3 days of fermentation time, respectively. Identification of folic acid in fermented vegetable extracts at optimum condition by LC-MS were carried out with the relative intensity for fermented spinach and broccoli were 0,48% and 0,56%, respectively, with a molecular weight of 459 m/z are identified as 5-methyl tetrahydrofolate.